Differential regulation of the Tor gene homolog drives the red/green pigmentation phenotype in the aphid Myzuspersicae. (February 2023) - Trissi, Nasser; Troczka, Bartlomiej J.; Ozsanlav-Harris, Luke; Singh, Kumar Saurabh; Mallott, Mark; Aishwarya, Veenu; O'Reilly, Andrias; Bass, Chris; Wilding, Craig S.
Abstract: In some aphid species, intraspecific variation in body colour is caused by differential carotenoid content: whilst green aphids contain only yellow carotenoids (β-, γ-, and β, γ-carotenes), red aphids additionally possess red carotenoids (torulene and 3, 4-didehydrolycopene). Unusually, within animals who typically obtain carotenoids from their diet, ancestral horizontal gene transfer of carotenoid biosynthetic genes from fungi (followed by gene duplication), have imbued aphids with the intrinsic gene repertoire necessary to biosynthesise carotenoids. In the pea aphid, Acyrthosiphon pisum a lycopene (phytoene) desaturase gene ( Tor ) underpins the red/green phenotype, with this locus present in heterozygous form in red individuals but absent in green aphids, resulting in them being unable to convert lycopene into the red compounds 3, 4-didehydrolycopene and torulene. The green peach aphid, Myzus persicae, separated from the pea aphid for ≈45MY also exists as distinct colour variable morphs, with both red and green individuals present. Here, we examined genomic data for both red and green morphs of M. persicae and identified an enlarged (compared to A. pisum ) repertoire of 16 carotenoid biosynthetic genes (11 carotenoid desaturases and five carotenoid cyclase/synthase genes). From these, we identify the homolog of A. pisum Tor (here called carotene desaturase 2 or CDE-2 ) and show through 3D modelling that this homolog can accommodate the torulene precursor lycopene and, through RNA knockdown feeding experiments, demonstrate that disabling CDE-2 expression in red M. persicae clones results in green-coloured offspring. Unlike in A. pisum, we show that functional CDE-2 is present in the genomes of both red and green aphids. However, expression differences between the two colour morphs (350–700 fold CDE-2 overexpression in red clones), potentially driven by variants identified in upstream putative regulatory elements, underpin this phenotype. Thus, whilst aphids have a common origin of their carotenoid biosynthetic pathway, two aphid species separated for over 40MY have evolved very different drivers of intraspecific colour variation. Graphical abstract: Image 1 Highlights: The aphid Myzus persicae displays intraspecific body colour variation with both red and green forms. CDE2 is the homolog of Tor in Acyrthosiphon pisum . Unlike in A. pisum, functional CDE-2 is present in the genomes of both red and green aphids. RNA KD of CDE-2 expression in red clones results in green-coloured offspring. >350 fold CDE-2 overexpression in red clones is potentially driven by upstream regulatory motifs.